Gastric emphysema secondary to severe vomiting: a comparative review of 14 cases. (27th September 2018) - Inayat, Faisal; Zafar, Fahad; Zaman, Muhammad Adnan; Hussain, Qulsoom
Abstract : Gastric emphysema is characterised by the presence of air within the wall of the stomach. The radiographic finding of gastric emphysema with hepatic portal venous gas is classically an ominous sign, associated with a high mortality rate. We report one case from our clinical experience and undertake a review of the previously reported cases of vomiting-induced gastric emphysema retrieved from the PubMed. A total of 14 cases were found to date. The mean age at the time of diagnosis was 45.6 years (range, 9 months to 81 years). Computed tomography abdomen was the frequently used diagnostic modality. Interestingly, conservative treatment led to a clinical cure and resolution of gastric emphysema as well as the associated hepatic portal venous gas in most of the patients. This review illustrates that vomiting-related gastric emphysema entails a more benign course and surgical intervention can be avoided with a prompt aetiology establishment in these patients.